Efficient anonymous password-based authenticated key exchange scheme - TAN Shi-chong; PANG Liao-jun; SU Wan-li; WANG Yu-min (Tongxin xuebao)
Password-based key exchange schemes was designed to provide entities communicating over a public network,and only sharing a（short） password with a session key（e.g.,the key was used for data confidentiality and/or integrity）.There has been much interest in password-authenticated key exchange protocol which remains secure even when users choose passwords from a small space of possible passwords,such as a dictionary of English words.A password-based authenticated key exchange scheme was proposed.The analysis shows that the scheme is secure against dictionary attack under the computational Diffie-Hellman intractability assumption,and preserves user privacy and achieves unlinkability.Furthermore,since denial-of-service（DoS） attacks have become a common threat,DoS-resistantance is a design consid-eration and the scheme is proved to be secure against denial-of-service attacks.